The Influence of NPL, OER, and CAR on the Profitability of Regional Development Banks in Indonesia - Ayuni, Novia Indah Tantri; Wahyudi, Setyo Tri (Contemporary Studies in Economic, Finance and Banking, 2026)
This study aims to determine the influence of Non-Performing Loans (NPL), OER, and Capital Adequacy Ratio (CAR) on the profitability of Regional Development Banks (BPD) in Indonesia, as measured by Return on Assets (ROA). The data used are BPD annual financial reports obtained from each bank's official website. The research object covers 23 Regional Development Banks in Indonesia with an observation period of 2019-2023. The analytical method used is panel data regression analysis with the Fixed Effect Model (FEM) approach, which was determined as the best model based on the results of the Chow and Hausman tests. The results show that partially NPL has a positive and significant effect on ROA, BOPO has a negative effect on ROA, while CAR does not show a significant effect on ROA. Simultaneously, these three independent variables are proven to affect BPD profitability. The findings of this study indicate that operational efficiency and credit risk management characteristics have a more dominant role in determining BPD profitability than capital adequacy factors. Therefore, the results of this study are expected to serve as a reference for BPD management and policymakers in formulating more effective strategies to improve the profitability of regional banks.